Verification of the Vitek Reveal System for Direct Antimicrobial Susceptibility Testing in Gram-Negative Positive Blood Cultures - Giulia Menchinelli; Damiano Squitieri; Carlotta Magrì; Flavio De Maio; Tiziana D’Inzeo; Margherita Cacaci; Giulia De Angelis; Maurizio Sanguinetti; Brunella Posteraro (Antibiotics)
Background/Objectives: The International Organization for Standardization (ISO) 20776-2:2021, which replaces ISO 20776-2:2007, focuses solely on the performance of antimicrobial susceptibility testing (AST) assays, emphasizing the ISO 20776-1 broth microdilution method as the reference standard. Consequently, categorical agreement (CA) and associated errors should not be applied. We verified the Vitek Reveal AST assay according to both ISO 20776-2:2021 and ISO 20776-2:2007 criteria. Methods: Samples from 100 simulated and clinical Gram-negative (GN) positive blood cultures (PBCs) were tested at a large teaching hospital. The simulated GN-PBCs were obtained from a hospital collection of isolates selected to represent diverse antimicrobial resistance profiles. The Reveal assay results were compared with those from the reference assay, and the time to result (TTR) for the Reveal assay was calculated. Results: The essential agreement rates were 96.1% (816/849) for simulated and 98.8% (929/940) for clinical GN-PBC samples. The bias values were −3.1 for simulated and −11.0 for clinical samples. The CA rates were 97.7% (808/827) for simulated and 99.2% (924/931) for clinical samples. The mean TTR ± SD (hours) for resistant organisms was significantly lower (4.40 ± 1.15) than that for susceptible, increased exposure (5.52 ± 0.48) and susceptible (5.54 ± 0.49) organisms. Conclusions: Our findings reinforce the potential of the Reveal assay as a valuable tool and support its implementation in clinical microbiology laboratories.